Fresno County Counsel Softball Team and Office BBQ at Wes Merritt's Backyard - Watkins, Howard::::::::: (1987)
Phil Jay holding up compass gift; background: Maureen Walsh, Jane Kuhn holding baby, Jeff Kuhn, Wes Merritt